Overexpression of lncRNA TCLlnc1 in gastric cancer predicts postoperative distant recurrence and poor survival. Issue 10 (5th September 2022) - Hu, Kan; Zhang, Yugui; Rong, Jun; Deng, Wensheng; Xiao, Benping
Abstract : TCLlnc1 was characterized as a lncRNA with oncogenic roles in T cell lymphoma, whereas its role in other diseases is unknown. We then explored the involvement of TCLlnc1 in gastric cancer. Paired gastric cancer and nontumor tissues from 66 gastric cancer patients were used to extract total RNA samples, which were used to perform RT-qPCRs to determine the expression of TCLlnc1. Plasma samples from these 66 gastric cancer patients and 66 healthy controls were also used to detect circulating TCLlnc1. Correlations of TCLlnc1 in both plasma and tissue samples with patients' clinical data were analyzed by chi-square t -test. The diagnostic value of TCLlnc1 for early-stage gastric cancer was analyzed with the receiver operating characteristic curve. A 5-year follow-up study was performed to explore the prognostic value of TCLlnc1 for the survival of gastric cancer patients. TCLlnc1 expression in tissue was increased in gastric cancer. Plasma TCLlnc1 was also increased in gastric cancer. Plasma TCLlnc1 was closely correlated with TCLlnc1 in gastric cancer tissues, but not TCLlnc1 in nontumor tissues. TCLlnc1 in plasma was only correlated with tumor distant metastasis, but not other clinical data. TCLlnc1 in plasma showed promising diagnostic value for stage I and II gastric cancer. Increased accumulation of TCLlnc1 was closely correlated with distant recurrence and poor survival during a 5-year follow-up. Therefore, TCLlnc1 is overexpressed in gastric cancer predicts postoperative distant recurrence and poor survival.